Picoballoon Probe - Kaderka, Jakub (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2020)
The Brno Observatory and Planetarium organised an international competition of PicoBalloon probes in March 2020. This article describes a technologies used in designing such probe. The probe is powered by a lithium battery which limits runtime to several days, but in comparison with the solar powered solutions it allows data transmission during the night. The probe is equipped with a pressure sensor and a GPS receiver. The telemetry is sent over an Internet of Things network. The probe was launched on 2nd of March and travelled over 1800 km in temperatures reaching -40 degrees Celsius.
Keywords: picoballoon; probe; LoRaWan; low-power; IoT